THE DESIGN OF HIGH PERFORMANCE PHOTO-TRANSISTOR BASED ON SEMICONDUCTOR NANO-MATERIALS - Zia Un Nabi; Salman Khan (Spectrum of Engineering Sciences, 2025)
Background: Phototransistors are key components in modern optoelectronics due to their high sensitivity and wide spectral response. However, enhancing performance metrics such as responsivity, detectivity and response time remains a significant challenge. Semiconductor nanomaterials offer promising solutions owing to their tunable band gaps, high carrier mobility and strong light-matter interaction. Objective: This study aimed to design and fabricate high- performance phototransistors using GaN-ZnO solid solution nanowires and WS₂– InGaZnO heterojunctions and to evaluate the impact of band gap engineering, synthesis parameters, plasmonic enhancement and heterostructure formation on device performance. Methods: GaN-ZnO nanowires with varying ZnO concentrations were synthesized and deposited onto Si/SiO₂ substrates to form the phototransistor channel. Device performance was evaluated under different synthesis temperatures and durations. Ag nanoparticles were introduced for plasmonic enhancement. Separately, WS₂–InGaZnO heterojunctions were fabricated via CVD and sputtering techniques. Phototransistor architecture employed bottom-gate configuration with Ti/Au source-drain electrodes. Key parameters such as photocurrent, responsivity, detectivity, response time and operational stability were analyzed. Results: Band gap tuning from 3.4 eV (GaN) to 2.6 eV (Zn-rich nanowires) enhanced visible light absorption. Optimal synthesis at 850 °C yielded highest responsivity (95.3 A/W) and detectivity (2.1 × 10¹¹ Jones). Ag nanoparticle decoration further improved responsivity to 131.7 A/W and reduced response time to 5.9 ms. The WS₂–InGaZnO heterojunction device exhibited superior performance with responsivity of 122.5 A/W, detectivity of 3.8 × 10¹¹ Jones, and excellent stability (91.7% retention over 50 cycles). Conclusion: The integration of band gap-engineered nanowires, plasmonic enhancements and heterojunction structures significantly advances phototransistor performance. These findings provide a strong foundation for developing next-generation, broadband and high-sensitivity photodetectors for practical optoelectronic applications.